Hybrid polymer networks of carbene and thiol ene. (5th September 2022) - Djordjevic, Ivan; Wicaksono, Gautama; Singh, Juhi; Singh, Manisha; Ellis, Elizabeth G.; Alraddadi, Maher A.; Dove, Andrew P.; Steele, Terry W.J.
Graphical abstract: Highlights: Acrylate-based hybrid polymer networks lack material design flexibility. Diazirine-grafted polyol, a novel carbene crosslinker of hybrid networks. Diazirine remains unreacted during thiol/ene crosslinking reaction. Carbene enables high level of control over hybrid network material properties. Abstract: Thiol/ene-based resorbable elastomers display tough elongation but lack adhesion to soft tissues. Carbene-based bioadhesives (e.g. CaproGlu) allow soft tissue adhesion, but the covalent crosslinks limit extensibility after photoactivation. Herein thiol/ene resorbable elastomers are combined with a carbene bioadhesive into a 3-component hybrid network by exploiting tunable photoactivation of each macromolecule independently or simultaneously. Dual crosslinking was monitored by photorheometry, where 405 nm initiates formation of a thiol/ene elastomeric network, followed by 365 nm activation of diazirine-grafted polycaprolactone tetrol (CaproGlu). Dynamic shear moduli, gelation point, elongation at break, and lap shear stress of the hybrid polymer network are evaluated with respect to absorbed light energy dose. Surface-exposed unreacted CaproGlu enables adhesion of the hybrid network to various substrates, as well as intermolecular crosslinking within the transparent matrix. The network morphology and functional group conversion is evaluated through scanning electron microscopy and infrared spectroscopy, respectively. For the first time, we demonstrate hybrid thiol/ene/diazirine double sided bioadhesives with tunable dynamic moduli in the range of 10–800 kPa and 160 kPa lap-shear adhesion strength.